COMPARATIVE STUDY ON BIO-BRIQUETTE PRODUCTION USING COCONUT SHELL AND SEASHELL: EFFECTS OF SIZE, RATIO, PYROLYSIS, AND BINDER - Dewi, Resti Nurmala; Perceka, Medal Lintas; Dia Utari, Siluh Putu Sri; Andrayuga, I Wayan; Azimatun, Muhamad Maulana Nur; Qurrahman, Taufiq; Arifin, Samsul; Ardiyanti, Putu Ayu; Pajriyanti, Nurlaela; Irwandi, Nurul Anisa (Indonesian Fisheries Research Journal, 2025)
Briquettes are seen as a substitute for alternative fuels generated through pyrolysis. A common type of briquette is charcoal made from coconut shells. However, they have poor combustion duration and excessive combustion smoke. It is thought that adding shells to coconut shell briquettes can increase their quality while making better use of waste since shells have adsorption characteristics. Hence, this study intended to produce shells briquettes on many main factors, namely pyrolysis time, particle size, raw materials ratio, and binder concentration. The method utilized pertained to preliminary study by blending pyrolyzed coconut shell charcoal, shells, and tapioca flour. In line with the American Standard Testing and Material (ASTM) 2014, proximate analysis was conducted using the Thermogravimetric Analysis 201; in contrast, briquette calorific value was determined using the GDY-1A bomb calorimeter, which is in compliance with ISO 1928:2020. According to the findings, the best shell briquettes was found at 2.5 hours pyrolysis durations with a particle size of 50 mesh, a raw material ratio of 3:1 (charcoal : shell) and 50% binder concentration with 13.53 ± 0.23% water content; 39.91 ± 0.31% volatile matter content, 15.70 ± 0.07% ash content, 67.66 ± 0.68% fixed carbon content) (P < 0.05), and a calorific value of 1,942.126 cal/g. Nonetheless, the results were not ideal as the calorific value was lower compared to full charcoal briquettes. Therefore, to improve proximate quality and combustion efficiency, it is required to combine seashells with other materials that are higher in carbon or to modify the method.